A REVISIT OF PECHMANN REACTION UNDER MICROWAVE RADIATION - Fauzia Anjum Chattha; Saeed Ahmed Nagra; Munawar Ali Munawar (Indonesian Journal of Chemistry, 2008)
A series of coumarins have been prepared by the Pechmann reaction of different phenols with ethyl acetoactate as well as malic acid using catalytic amount of sulfuric acid under microwave irradiation for few seconds.